Reducing the vulnerability of coastal communities in the Caribbean through sustainable mangrove management. (1st September 2021) - Soanes, L.M.; Pike, S.; Armstrong, S.; Creque, K.; Norris-Gumbs, R.; Zaluski, S.; Medcalf, K.
Abstract: The 2017 Atlantic storm season caused widespread damage to Caribbean nations including the British Virgin Islands. The winds and rainfall associated with Hurricanes Irma and Maria played their part in the destruction of infrastructure, livelihoods and the environment. With an increased interest in nature-based solutions to reduce flood risk, increasing the resilience of coastal communities and a focus on three of the most vulnerable communities in the Virgin Islands, we report on the use of flood risk vulnerability models based on remotely sensed satellite data and ecosystem services principles. Models were created with 4 primary aims to: (1) monitor the impact of storms and the recovery of mangroves, (2) assess the risk of flooding due to hurricane storm surges and extra-tropical storms (ground seas), (3) model opportunity areas for the restoration of red mangroves ( Rhizophora mangle) and buttonwood ( Conocarpus erectus) and (4) model and produce maps highlighting the predicted benefits that mangrove restoration will have on vulnerable coastal communities. Results highlight that between 75 and 94% of red mangroves in the three communities were negatively impacted by hurricanes in 2017. However, vulnerability models predict that even small-scale mangrove restoration initiatives can help to reduce the flood risk of homes and infrastructure up to 475 m inland. This work has provided the rationale for mangrove restoration in the Virgin Islands and presents an important tool for expansion across the wider Caribbean region that can be used to inform coastal restoration and resiliency building activities. Highlights: NDVI analysis revealed that up to 94% of mangroves were impacted by Hurricane Irma. Flood risk vulnerability maps identified coastline most vulnerable to storm surges. Small-scale mangrove restoration can provide flood protection up to 475m inland. Mangrove restoration can reduce flood risk to at least 700 buildings.